R&D cooperation and R&D intensity: theory and micro-econometric evidence for german manufacturing industries - Ulrich Kaiser; Georg Licht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
This paper develops a three stage oligopoly game for R&D cooperation, R&D expenditure and product market competition. In the first stage, firms decide whether or not to conduct R&D in cooperation with other firms. In the second stage the level of R&D investment is determined. Finally, firms compete in a Cournot?oligopoly product market. While earlier models on R&D cooperation only considered process innovation, the model presented here also takes product innovation into account. It is shown that the optimal R&D investment has virtually the same structure for both process and product innovation. The main hypothesis of our theoretical model are tested in the empirical part of this paper.
Keywords: C24; L13; C25; O31; 330; R&D cooperation; R&D intensity; spillovers; nested logit model; Minimum Distance Estimator; Industrielle Forschung; Forschungskooperation; Forschungskosten; Spillover-Effekt; Oligopol; Schätzung; Theorie; Deutschland